Gaya Bahasa Retoris Rosianna Silalahi Dalam Acara Talkshow Mencari Tahu Kompas tv - Raisa Wardani; Intan Munawarah; Wina Almunadia (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
This research aims to describe the form of Rosianna Silalahi's rhetorical language style in the talk show llll. "Finding Out" on the KOMPASTV channel. The data sources in this research are primary data and secondary data. The data source in this research is the talk show hosted by Rosianna Silalahi "Finding Out" on the Kompas TV channel. Researchers chose 2 shows (episodes) from the program with the theme episode I "Gibran: I'm Not the Mayor of Karbitan, But Bocil Dynasty (Jokowi's Discourse for Three Periods in 2024)", and episode II "Sri Mulyani bluntly clarifies the storm at the Ministry of Finance". Data collection techniques were carried out using listening, note-taking and transcript techniques. Rhetorical language style in 2 talk shows hosted by Rosianna Silalahi "Finding Out" on the Kompas TV channel. In the episode I Gibran: I Am Not the Mayor of Karbitan, But Bocil Dynasty (Jokowi's Discourse for Three Periods in 2024)", we found 7 alliterative language styles, 2 euphemisms, 1 chiasmus, 9 assonations, 9 asidentons 2 data, 5 data polysidentons, 1 data paradox and 19 data corrections. Furthermore, in the episode II broadcast "Sri Mulyani's outspoken clarification of the storm at the Ministry of Finance", we found 8 data of alliterative rhetorical language style, 2 data of kiamus, 2 data of asindenton, 1 data of polysidenton, 2 data of paradox and 6 data of correction. If it is described, it can be concluded that the results of the language style are 2 utterances of euphemism, 3 utterances of chiamus, 3 utterances of paradox, 4 utterances of asyndeton, 6 utterances of polysyndeton, 9 utterances of assonation, 15 utterances of alliteration and 25 utterances of correction.